1978
DOI: 10.1002/kin.550100906
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of activation energies of radical–molecule metathesis reactions with enthalpic, polar, and steric parameters

Abstract: It is shown that the activation energies E OF chlorine atom abstraction by cyclohexyl radicals and hydrogen atom abstraction by C1 atoms from polychloroalkanes can be correlated with the bond dissociation energies D and the Taft polar and steric substituent constants u* and E , by the expression:where I ! & and ALI represent the differences between the E and D values of a given substrate and those of a reference compound (CHB substituted substrate) and a, p, and 6 are the corresponding correlation coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Furthermore, CCll (X=C1) and CFCh (X=F) have almost equal (T* values, 2.96 and 3.08, respectively. Therefore the difference in Ecl of 1.9 kcal/mol, which is primarily responsible for the markedly reduced re- [12] and [17]. Average values from the present work.…”
Section: Effect Of Substitution By An F Atom On Reactivitymentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, CCll (X=C1) and CFCh (X=F) have almost equal (T* values, 2.96 and 3.08, respectively. Therefore the difference in Ecl of 1.9 kcal/mol, which is primarily responsible for the markedly reduced re- [12] and [17]. Average values from the present work.…”
Section: Effect Of Substitution By An F Atom On Reactivitymentioning
confidence: 57%
“…Using the correlation in eq. (I), Katz and Rajbenbach [12] have shown that for the series of C1transfer reactions of c -CsH11 radicals with chloromethanes and chloroethanes, having the general form CC13X, the activation energy difference AEcl is given by…”
Section: Effect Of Substitution By An F Atom On Reactivitymentioning
confidence: 99%
“…This behavior differs from the behavior observed in the C1-transfer reactions of cyclohexyl radicals [2]. There the A factors are practically constant so that the reactivity trends reflect the effect of structural parameters on the activation energy of the reaction [21]. It is worth noting, however, that despite this difference, the logarithms of the rate constants of the C1-transfer reaction of EtySi and c-C6Hll radicals are linearly dependent.…”
Section: Relative Arrhenius Parameters Of C1-transfer Reactions Of Etmentioning
confidence: 79%
“… 28 The number of Cl radicals liberated from the solvent can be explained by the bond dissociation energies. In chloroform, o -DCB and chlorobenzene molecules, the bond dissociation energies of C–Cl bonds are 318.8 kJ mol −1 , 40 385.8 kJ mol −1 41 and 399.6 kJ mol −1 , 42 respectively. Therefore, the Cl radicals in chloroform were most easily extracted from the solvent under the same UV ozone conditions, while Cl radicals were the most difficult to liberate from chlorobenzene.…”
Section: Resultsmentioning
confidence: 99%